Factors Influencing on Students’ Decisions to Study at Luang Prabang Traditional Arts College - Pheangkhamsone, Phoungern (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aims to Examine the level of factors influencing the decisions of students who chose to study at the College of Traditional Arts; Examine the level of decision-making among students who chose to study at the College of Traditional Arts; and Analyze the factors affecting the decisions of students who chose to study at the College of Traditional Arts. The sample group consisted of 106 students currently enrolled at the College of Traditional Arts. The research instrument was a questionnaire, and data were analyzed using SPSS software, employing frequency, percentage, mean, standard deviation, and multiple regression analysis. The results showed that, overall, the factors influencing students' decisions to study at the College of Traditional Arts were at a high level. These included financial factors, institutional reputation, personal factors, curriculum, atmosphere and environment, and family influence. Regarding the level of decision-making, findings indicated that students’ decisions to study at the College of Traditional Arts were also at a high level. Key reasons included affordability of tuition, the potential for academic qualifications to support career advancement and salary growth, and the expectation of receiving social recognition after graduation. Finally, the analysis revealed that financial factors, institutional factors, environmental factors, public relations, and social factors had a statistically significant effect on students' decisions to study at the College of Traditional Arts (at the 0.05 level).